2006
DOI: 10.1001/archinte.166.8.846
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Impaired Diurnal Blood Pressure Variation With a Subsequent Decline in Glomerular Filtration Rate

Abstract: Background: Most healthy people exhibit a decrease in systolic blood pressure (SBP) at night. A drop of less than 10% from mean daytime values (nondipping) is associated with chronic kidney disease, insulin resistance, and cardiovascular events. Whether nondipping precedes a decline in renal function remains unclear. We hypothesized that nondipping would predict a decline in the glomerular filtration rate (GFR) over time.Methods: Consecutive patients referred for ambulatory blood pressure monitoring were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
139
6
7

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(167 citation statements)
references
References 56 publications
7
139
6
7
Order By: Relevance
“…However, when the 24-hour period was assessed, this behavior pattern was not observed. These findings, in general, differ from those found in literature [14][15][16]18,19 .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, when the 24-hour period was assessed, this behavior pattern was not observed. These findings, in general, differ from those found in literature [14][15][16]18,19 .…”
Section: Discussioncontrasting
confidence: 99%
“…After the biochemical dosages, we found that, except for the higher levels of HDL-c in ND patients, the remaining variables did not present statistical significance, findings that are similar to those observed in other studies 15,16 . Despite the lower HDL-c in non-dipper patients, there was no correlation to higher risk of lesions in target-organs.…”
Section: Dm -Diabetes Mellitus; MI -Myocardium Infarction; Dlp -Dislisupporting
confidence: 85%
See 3 more Smart Citations